Characterisation of cholinesterase and histopathological features of brain of Clarias gariepinus following exposure to cadmium - Fadzil, Nadia Izati; Ahmad, Siti Aqlima; Yasid, Nur Adeela; Sabullah, Mohd Khalizan; Mohd Daud, Hassan; Khalid, Ariff; Padrilah, Siti Nadzirah; Shukor, Mohd Yunus (Triveni, 2019)
Aim : Cholinesterase (ChE) inhibition and histopathological features of brain tissues of Clarias gariepinus were investigated with a purpose to develop biomarkers for monitoring heavy metals. Methodology : The effects of cadmium toxicity on were assessed by ChE inhibition and characterisation of ChE by affinity chromatography and histological variations in brain tissues were studied by H&E staining under light microscope. Results : The purified enzyme gave 10.58 fold purification with the recovery of 12% with specific activity of 159.729 U-1 mg . The Michaelis-Menten constant (K ) m and V value obtained was 1.985 mM max -1 -1 and 0.4479 µmol min mg , respectively. The enzyme showed the ability to hydrolyse acetylthiocholine iodide (ATC) at a faster rate compared to other two synthetic substrates, propionylcholine iodide (PTC) and butyrylthiocholine iodide (BTC). ChE showed highest activity at 35°C in Tris-HCl pH 7.5. The metal inhibition study also found the maximal inhibitory concentration (IC ) 50 -1 value for cadmium to be 0.6517 mg l . Histological study revealed decrease in the number of cells, degeneration of Purkinje cells, increased aggregation area and cells necrosis. Interpretation : Inhibition of cholinesterase activity and degeneration of Purkinje cells observed in the present study can be used as a tool for further developing a biomarker for detecting heavy metals in the aquatic ecosystems. C. gariepinus